Tracking Global Demand for Emerging Market Sovereign Debt - Arslanalp, Serkan; Tsuda, Takahiro (Washington, D.C. : International Monetary Fund, 2014)
This paper proposes an approach to track USD 1 trillion of emerging market government debt held by foreign investors in local and hard currency, based on a similar approach that was used for advanced economies (Arslanalp and Tsuda, 2012). The estimates are constructed on a quarterly basis from 2004 to mid-2013 and are available along with the paper in an online dataset. We estimate that about half a trillion dollars of foreign flows went into emerging market government debt during 2010-12, mostly coming from foreign asset managers. Foreign central bank holdings have risen as well, but remain concentrated in a few countries: Brazil, China, Indonesia, Poland, Malaysia, Mexico, and South Africa. We also find that foreign investor flows to emerging markets were less differentiated during 2010-12 against the background of near-zero interest rates in advanced economies. The paper extends some of the indicators proposed in our earlier paper to show how the investor base data can be used to assess countries' sensitivity to external funding shocks and to track foreign investors' exposures to different markets within a global benchmark portfolio.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet